Over‐expression of DEC1 inhibits myogenic differentiation by modulating MyoG activity in bovine satellite cell. Issue 12 (19th June 2018) - Huang, Yongzhen; Lai, Xinsheng; Hu, Linyong; Lei, Chuzhao; Lan, Xianyong; Zhang, Chunlei; Ma, Yun; Zheng, Li; Bai, Yue‐Yu; Lin, Fengpeng; Chen, Hong
Abstract : Differentiated embryo chondrocyte 1 (DEC1), a member of basic‐helix‐loop‐helix transcription factor Bhlhe40, also called stimulated by retinoic acid 13, STRA13, plays an important role in the regulation of adipogenesis, tumorigenesis, peripheral circadian output, response to hypoxia, and development of metabolic syndrome. Previous studies suggested that DEC1 was involved in skeletal muscle development; however, its precise role in myoblast differentiation has not been determined. In the present study, we showed that DEC1 expressed ubiquitously in different bovine tissues and was down‐regulated in differentiated bovine satellite cells. Expression of muscle specific transcription factors (Myf5, MyoD, MyoG, and MHC) was significantly down‐regulated when DEC1 was over‐expressed by both CoCl2 ‐simulated hypoxia and Adenovirus‐mediated transduction in bovine satellite cells. Consistent with that, promoter analyses via luciferase reporter assay also revealed that overexpression of bovine DEC1 could inhibit MyoG promoter activity. In conclusion, overexpression of DEC1 blocked myogenesis by inhibiting MyoG promoter activity in bovine. Our results provided a new mechanism for the muscle growth, which would contribute to increase cattle meat productivity. Abstract : DEC1 was ubiquitously expressed in most tissues in bovine and down‐regulated in differentiating bovine satellite cells. Either CoCl2‐simulated hypoxia or ectopic expression of DEC1 blocked bovine myoblast differentiation. Over‐expression of bovine DEC1 inhibited MyoG promoter activity. The present study gives new insight into the mechanisms involved in myogenic differentiation.